Reflective Thinking Skills: A Survey Study on Biology Learning in Senior High School - Fadillah, Hikmah Nur (Jurusan Pendidikan Biologi - Universitas Siliwangi, 2024)
Students need to have 21st-century skills in learning to face various global demands and challenges. Reflective thinking skills are fundamental skills that are important for students to have in 21st-century learning. Reflective thinking is the ability of individuals to be directed and precise in realizing, analyzing, evaluating, and motivating their learning process. This study aimed to see the students' critical thinking skills at SMA Negeri 3 Wajo. The research method used in this study is the qualitative descriptive research method. The sample of this study was students of SMA Negeri 3 Wajo. The number of samples in this study was 100 students. Students' reflective thinking skills were measured using questionnaire instruments. The indicators used to measure students' reflective thinking skills consist of four: Habitual Action, Understanding,Â Reflection and Critical Reflection. Based on the results of the analysis that has been done, the reflective thinking skills of SMAN 3 Wajo students are still in the low category with a percentage of 37.95% and need to be improved for each indicator of reflective thinking skills. Reflective thinking skills can be trained and improved through appropriate learning models and methods.